Explainable Machine Learning Techniques for Criticality Prediction of Software Change Requests - Santos, Amanda Q. R. dos; Silva, José R. da; Lins, Renata F.; Prudencio, Ricardo B. C. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2024: Anais do XXI Encontro Nacional de Inteligência Artificial e Computacional, 2024)
Text classification is an essential task in several real applications, commonly involving the use of Natural Language Processing (NLP) and Machine Learning (ML). Specifically, in the context of software testing, text classifiers have been applied to the analysis of Change Requests (CRs) documents, which are reports that report errors found in the software under test. Prioritizing critical CRs is crucial for more effectively maintaining the quality of developed products. This article explores the use of eXplainable AI (XAI) algorithms for the inspection of CR criticality classifiers, facilitating the interpretation and justification of decisions made by the ML model. Once a CR is classified as critical, explanations are generated to identify important characteristics that help understand why the error reported by the CR was considered critical. In a case study, we implemented the LIME technique to provide interpretable explanations of the predictions made by an XGBoost model, applied to a database extracted from a real industrial context of mobile device development. The results show that XAI can increase confidence in ML model decisions by highlighting the most significant terms in critical and non-critical CRs.